POTENTIAL EMBRYOTOXIC EFFECT STUDY OF MINOXIDIL-CONTAINING LOTION IN EXPERIMENT WITH FEMALE RATS - Turkina, V.A.; Chemodurova, N.Ye.; Pryzyglei, H.V.; Кuzminov, Y.B. (World of Medicine and Biology, 2021)
The purpose of this study was to establish maternal safety of topical preparation containing 5 % minoxidil, as well as safety for fetal development, fetus-maternal functional responses in experiments with laboratory rats using doses and methods of administration recommended by the manufacturer. Based on the results obtained under these experimental conditions, a lotion containing 5 % minoxidil does not cause changes to the reproductive system of rats and does not demonstrate embryotoxic effect.
Keywords: minoxidil; androgenetic alopecia; embryotoxic effect